2012
DOI: 10.1177/000348941212100808
|View full text |Cite
|
Sign up to set email alerts
|

Spectral- and Cepstral-Based Acoustic Features of Dysphonic, Strained Voice Quality

Abstract: Cepstral- and spectral-based measures that have been previously studied in dysphonia characterized by breathiness and roughness are effective in distinguishing strained dysphonia from normal voice quality. The utility of these acoustic measures is supported by their moderate-to-high relationship with perceptually rated strain severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 31 publications
(8 reference statements)
2
28
1
7
Order By: Relevance
“…Therefore, the finding that patients showed higher F0 values than the normal controls could be explained by their voice quality characteristics. In a study by Lowell et al [25], in which voices with high roughness were compared to normal voices, CPP F0 of speakers with high roughness was significantly higher (227.61 ± 23.58 Hz) than that of speakers with normal voices (178.40 ± 24.21 Hz). Further, CPP F0 showed an increased pattern for speakers with strained voices.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the finding that patients showed higher F0 values than the normal controls could be explained by their voice quality characteristics. In a study by Lowell et al [25], in which voices with high roughness were compared to normal voices, CPP F0 of speakers with high roughness was significantly higher (227.61 ± 23.58 Hz) than that of speakers with normal voices (178.40 ± 24.21 Hz). Further, CPP F0 showed an increased pattern for speakers with strained voices.…”
Section: Discussionmentioning
confidence: 99%
“…Cepstral measures have been shown to highly correlate with dysphonia severity (Awan & Roy, 2006), thus a possible explanation for the disparity between the study by Lowell et al (2012) and Brinca et. al.…”
Section: Introductionmentioning
confidence: 92%
“…Unfortunately, a study examining the correlation between 19 common acoustic measures and a clinician-based perceptual voice assessment protocol, the Grade, Roughness, Breathiness, Asthenia, Strain (GRBAS) scale, found that no acoustic measure was well-correlated with strain (Bhuta, Patrick, & Garnett, 2004). More recently, the perception of strain has been shown to have strong relationship with cepstral measures and moderate relationship with spectral measures in a group of dysphonic speakers with predominately strained voice quality (Lowell, Kelley, Awan, Colton, & Chan, 2012). However, when the primary factor of the cepstral measure – cepstral peak prominence -- was examined in a group of individuals with nonhomogeous diagnoses, no significant correlation was found between cepstral peak prominence and the perception of strain (Brinca, Batista, Tavares, Gonçalves, & Moreno, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Increased high-frequency spectral energy may be associated with dysphonia, and studies have also demonstrated that a small L/H SD is also present in speakers with dysphonia. 22 KayPENTAX's ADSV program also computes a multivariate index measure, the CSID, based on regression algorithms that incorporate the cepstral and spectral measures of CPP, L/H ratio, and L/H ratio SD. The CSID approximates a 100-point severity scale that can be compared with auditory-perceptual ratings and has been validated for the CAPE-V sentences in adults.…”
Section: Discussionmentioning
confidence: 99%